Gender issues in Alice Tan-Gonzales' Ilongga madamu nga guya. - Lagnason, Abigail D.
Gender inequality has been a never-ending issue. Although some feminists are aware that equality is far achieved, they are still determined to work toward the achievement of such equality. Despite the fact that the society has become more open-minded to different contemporary issues, in the Philippines, women are still suffering from different kinds of exploitation and oppression. There are many factors, which lead to women's exploitation and oppression, and one of these is the fact that society establishes roles for both sexes, Gender roles limit what both males and females can do. There are certain things that society sets on what specific roles a man and a woman must do.